Clinical efficacy and safety of acupuncture combined with statin in dyslipidemia: A meta-analysis and system review - Liu, Xinyu; Chen, Kun; Chen, Fujian (Medicine (Baltimore), 2024)
Background: This study aims to systematically evaluate the clinical efficacy and safety of acupuncture in combination with statin therapy compared to statin monotherapy for the treatment of dyslipidemia. Methods: A comprehensive search for relevant randomized controlled trials assessing the clinical efficacy of acupuncture and statin combination in the treatment of dyslipidemia was conducted. Databases including PubMed, EMbase, Web of Science, Cochrane Library, China National Knowledge Infrastructure, China Biology Medicine disc, Wanfang database, and China Science and Technology Journal Database were searched up to October 27, 2023. Results: Sixteen Chinese-language studies involving a total of 1333 subjects were included for analysis. The meta-analysis revealed that the total effective rate of acupuncture combined with statin was significantly higher than that of statin alone (odds ratios = 3.32, 95% confidence intervals [CI] = 2.33 to 4.72). Furthermore, the combination of acupuncture with statin treatment resulted in a significant reduction in triglyceride levels (mean differences [MD] = −0.72 mmol/L, 95% CI = −1.05 to −0.4), total cholesterol levels (MD = −0.79 mmol/L, 95% CI = −1.07 to −0.51), low-density lipoprotein cholesterol levels (MD = −0.61 mmol/L, 95% CI = −0.95 to −0.27) and traditional Chinese medicine syndrome integral (MD = −1.32, 95% CI = −1.75 to −0.89), compared to statin treatment alone. Additionally, the high-density lipoprotein cholesterol level was higher in the combined acupuncture and statin treatment group than in the statin treatment alone group (MD = 0.44 mmol/L, 95% CI = 0.09 to 0.79). Notably, the rate of adverse reactions reported with combined acupuncture and statin treatment was lower than that with statin therapy alone. Conclusion: Our findings support the potential of acupuncture combined with statin as a viable clinical treatment option for dyslipidemia. However, it is important to note that current research on the mechanism of acupuncture for lipid-lowering has not yielded definitive results, and there are inherent biases in the conducted clinical studies.